2015
DOI: 10.1002/ptr.5501
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Resveratrol on Receptor for Advanced Glycation End Products (RAGE) Expression and Oxidative Stress in the Liver of Rats with Type 2 Diabetes

Abstract: Incidence of diabetes mellitus is dramatically growing in the world. Oxidative stress, advanced glycation end products (AGEs) and receptor for AGE (RAGE) play key role in the pathogenesis of diabetes. Little is known about resveratrol effects on the liver. We hypothesize that resveratrol may exert a hepatoprotective effect in diabetic rats. Male rats with diabetes were treated with or without resveratrol at 1, 5 and 10 mg/kg body weight for 30 days. Total AGEs and malondialdehyde (MDA) levels in liver tissues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 41 publications
0
41
0
1
Order By: Relevance
“…Jing et al showed that oral supplementation of RSV (0.75 mg/kg) three times a day for 4–8 weeks remarkably suppressed the expression of RAGE and RAGE/ nuclear factor kappa B (NF‐κB) signaling pathway in streptozotocin (STZ)‐induced diabetes mellitus (DM) rats . Findings of two studies by Moridi and Khazaei revealed a significant reduction in the expression of RAGE following 1, 5, and 10 mg/kg/d of dietary RSV for 30 days in diabetic rats; however, serum AGE levels did not significantly change . Al‐Hussaini et al achieved different results compared to those by Moridi and Khazaei; the authors expressed that oral supplementation with 5 mg/kg/d of RSV for 45 days caused a significant reduction in the accumulation of AGEs; however, no significant changes were observed for the expression of RAGE in diabetic rats .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Jing et al showed that oral supplementation of RSV (0.75 mg/kg) three times a day for 4–8 weeks remarkably suppressed the expression of RAGE and RAGE/ nuclear factor kappa B (NF‐κB) signaling pathway in streptozotocin (STZ)‐induced diabetes mellitus (DM) rats . Findings of two studies by Moridi and Khazaei revealed a significant reduction in the expression of RAGE following 1, 5, and 10 mg/kg/d of dietary RSV for 30 days in diabetic rats; however, serum AGE levels did not significantly change . Al‐Hussaini et al achieved different results compared to those by Moridi and Khazaei; the authors expressed that oral supplementation with 5 mg/kg/d of RSV for 45 days caused a significant reduction in the accumulation of AGEs; however, no significant changes were observed for the expression of RAGE in diabetic rats .…”
Section: Resultsmentioning
confidence: 95%
“…Given the fact that the NF‐κB pathway is involved in both the expression and signaling of RAGE, this study suggests that RSV suppresses NF‐κB–RAGE/AGE–NF‐κB signaling . Khazaei et al demonstrated that RSV modulated the expression of elevated RAGE in the liver tissue of diabetic rats; however, the possible mechanisms are unknown . Furthermore, Zhang et al suggest that the inhibition of peroxisome proliferator‐activated‐receptor‐γ (PPARγ) is a possible mechanism for the modulatory effect of RSV on the expression of RAGE .…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of IAPP fibrillization is most likely just one of the antidiabetic mechanisms by which resveratrol acts in humans. Indeed, when tested in diabetic rat models, resveratrol was able to reduce hepatic RAGE expression and plasma glucose levels, at the same time enhancing peripheral insulin sensitivity . In clinical trials, short‐term resveratrol supplementation (1 g/day for 45 days) significantly decreased systolic blood pressure, fasting plasma glucose levels, glycated hemoglobin (A1c), insulin, and insulin resistance in type 2 diabetic patients already receiving antidiabetic medication when compared to the placebo group .…”
Section: Unveiling Natural Leadsmentioning
confidence: 99%
“…Furthermore, RSV was recently shown to improve IRS-1 mediated insulin signaling through inhibition of protein tyrosine phosphatase (PTP) 1B expression in liver and muscle of diabetic rats [71]. In addition, RSV was reported to downregulate the expression of receptor for AGE (RAGE) in diabetic rat tissues [72, 73]. Therefore, RSV amelioration of AGE-induced dysregulated insulin signaling through the inhibition of AGE production and activities may partly contribute to its antihyperglycaemic property in DM.…”
Section: Mechanisms Of Protection Of Resveratrol In Diabetes Mellimentioning
confidence: 99%